Windbreaks working as barriers to high speed winds for protection of electric power transmission lines and towers. (December 2017) - Barbosa, Carlos D.F.; Severino, Carlos; Matsumoto, Edson; Guijun, Liu; Labaki, Lucila; Leone, Marcos; Barbosa, Paulo S.F.; Vatavuk, Paulo; Camargo, Rogerio P.; Forti, Tiago
Abstract: The effects of bad weather conditions on transmission lines associated with high speed wind events have concerned not only industry players, but also the government and consumers of electricity. Recently in Brazil, events of this nature have caused large-scale disruptions in the supply of electricity, resulting in direct economic losses throughout the chain of production and consumption. This paper aimed to propose a methodology for reduction of the occurrence of faults in transmission lines and towers related to high speed wind events and gusts, including a safety analysis and recommendation for corrective maintenance. Results are based on a R&D project, with its development including: a) the identification of transmission line faults occurred in Brazil, with wind events as the main underlying cause; b) the description of wind tunnel tests and computational fluid dynamics (CFD) modeling results aiming at exploring the effectiveness of windbreaks (tree rows alongside the transmission line corridors) as a mean to reduce wind impacts against towers and transmission lines; c) recommendations to reduce the risks of collapse of the transmission infrastructure of large-scale electric power systems which are exposed to extreme weather events. The research development was supported by State Grid Brazil, as a part of their R&D investment in its subsidiary company, Porto Primavera Transmissora de Energia (PPTE) during the years of 2014 and 2015. Highlights: Selection of the most appropriate tree species; the best arrangement and spacing Reduction in wind speed up to 59% in relation to the velocity free wind flow Simulations with two barriers showed significantly improvement in the protection. Useful: improves reliability of transmission lines in extreme weather wind events. Effectiveness of the windbreak: wind speed reduction, mitigating risks of collapse.